(untitled) - Royce, Walker (Reading, Mass., 1998)
This book captures a sofware management perspective that emphasizes a balanced view of these elements: theory and practice, technology and people, customer value and provider profitability, strategies and tactics.
Keywords: Phần mềm máy tính,Computer software; Phát triển,Development,Management; Quản trị